Arabinan-rich pectic polysaccharides from buriti (Mauritia flexuosa): An Amazonian edible palm fruit. (20th May 2015) - Cantu-Jungles, Thaisa Moro; Almeida, Carolina Pierobom de; Iacomini, Marcello; Cipriani, Thales R.; Cordeiro, Lucimara M.C.
Highlights: Two pectic polysaccharides were purified from pulp of buriti fruits. A branched arabinan linked to rhamnogalacturonan-I was characterized. A high methyl esterified homogalacturonan was also present. The hypothesis that pectin is the main non-cellulosic polymer in palms was supported. ABSTRACT: Primary cell wall polysaccharides from aqueous extract of buriti fruit pulp ( Mauritia flexuosa, an exotic tropical palm) were isolated and characterized. After freeze–thaw and α-amylase treatments, extracted polysaccharides were purified by sequential ultrafiltration through membranes. Two homogeneous fractions were obtained, SBW-100R and SBW-30R (Mw of 126 kDa and 20 kDa, respectively). Monosaccharide composition, methylation and 13 C NMR analysis showed that fraction SBW-100R contained a (1 → 5)-linked arabinan, branched at O -3 and O -2 positions, linked to a type I rhamnogalacturonan. Low amounts of these polymers were also present in fraction SBW-30R according to 13 C NMR analysis and monosaccharide composition. However, a high methyl esterified homogalacturonan (HG) was present in higher proportions. These results reinforce previous findings present in literature data which indicate that pectic polysaccharides are found in high amounts in primary cell walls of palms, which are commelinid monocotyledons.